Genomic resources for pigeonpea - Odeny, Damaris Achieng; Shah, Tushaar; Saxena, Rachit K. (2016)
Pigeonpea is increasingly playing a critical role in the lives of many farmers in the semi-arid tropics, where it is grown for both subsistence and commercial use. The recent availability of genomic resources opened a new chapter in pigeonpea breeding and has led to a lot of progress in a relatively short period of time. Molecular markers have been developed and used for germplasm characterization. Both whole genome and transcriptome sequences have further improved our understanding of the genome. This review provides a summary of genomic resources available for pigeonpea breeding and also briefly discusses the way forward for pigeonpea improvement.